P08.10 Combining STING-agonist with radiotherapy remodels tumor immune microenvironment in human malignant pleural effusions. (21st September 2022) - Zirnbauer, R; Ammon, D; Mosleh, B; Hoda, MA; Fabits, M; Laengle, J; Bergmann, M
Abstract : Background: Radiotherapy (RT) serves as a major backbone for different standard therapies for various solid malignancies. It has proven to be a double-edged sword unpredictively evoking immunogenic or immunosuppressive changes in the tumor immune microenvironment (TIME). The combination of RT with stimulator of interferon genes (STING) agonists provides the prospect of robustly remodeling the local TIME, thereby enhancing the pro-inflammatory cytokine production, as well as altering the phenotypes of the local inhabitants. In pre-clinical mouse models, it has shown to be superior to RT monotherapy. However, with a void in human test systems modeling the TIME there is little pre-clinical evidence that this is the case in the human organism. Material and methods: We developed a novel human ex vivo culture platform derived from malignant pleural effusions (MPE) collected from patients (n=9) with metastasized solid tumors (breast, pancreatic, gastric, ovarian and colon cancer). Upon concomitant treatment with a STING agonist (10 μM ADUS-100) and RT (1×8 Gy), changes in T cell activation and secretory cytokines were measured following 24 h of incubation. T cell activation and degranulation was determined by measuring CD69 and CD107a expression using flow cytometry (FCM). Secreted immunomodulatory cytokines (INF-α, INF-β, INF-γ, IL-6, IP-10, RANTES, TNF-α, MIP1-α, MIP-1β, MCP-1, IL-8, IL-10, IL-1rα) were measured with the Human LUMINEX Discovery Assay. Results: Treatment with RT alone lacked the ability to induce immunostimulatory changes and caused a twofold increase in death of cytotoxic (CD8+) and helper (CD4+) T cells in cultures derived from MPE. Combining RT with a STING agonist however significantly induced the activation (CD69+) and degranulation (CD107a+) of cytotoxic and helper T cells, at least doubling the respective populations. The secretion of pro-inflammatory cytokines such as INF-α, INF-β, INF-γ, IL-6, IP-10 and TNF-α was also markedly enhanced upon combinatory treatment. Conclusion: We established a novel human ex vivo system to monitor therapeutically induced changes in the local TIME of MPE. The STING agonist robustly remodels the TIME into a pro-inflammatory state inducing a local destructive inflammatory stimulus and chemoattractant properties. In prospect of harnessing the cytotoxic power of RT, as well as immunostimulatory effects of the STING pathway, we propose this combination as a potential therapeutic regimen for solid malignancies. Disclosure Information: R. Zirnbauer: None. D. Ammon: None. B. Mosleh: None. M.A. Hoda: None. M. Fabits: None. J. Laengle: None. M. Bergmann: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Boehringer Ingelheim.